1988
DOI: 10.1111/j.1399-3054.1988.tb04936.x
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nitrogen assimilation in plants of Austrlian rainforest communities

Abstract: In a study of the plant communities of two Australian rainforests, it was found that pioner species had high levels of nitrate reductase (EC 1.6.6.1) and were predominantly leaf nitrate assimilators. Under‐ and over‐storey species had low levels of shoot and root nitrate reductase activity, and many of them showed little capacity for nitrate reduction even when nitrate ions were freely available. Although closed‐forest species have lower levels of nitrate reductase than those of gaps and forest margins, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 28 publications
4
53
0
1
Order By: Relevance
“…Evidence from a variety of ecosystems indicates that N-partitioning through preferential uptake of particular N forms is not uncommon. Early and late successional tree species have been found to display differential uptake of NO À 3 versus NH þ 4 , respectively, which, due to variation in the availability of these N-forms along successional gradients, affects tree distributions (Stewart et al 1988;Kronzucker et al 1997;Aidar et al 2003). In N-limited arctic and alpine tundra plant communities, species composition was found to correlate with the partitioning of differentially available forms of N, with dominance being linked to a species' ability to exploit the most abundant N-form (McKane et al 2002;Ashton et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from a variety of ecosystems indicates that N-partitioning through preferential uptake of particular N forms is not uncommon. Early and late successional tree species have been found to display differential uptake of NO À 3 versus NH þ 4 , respectively, which, due to variation in the availability of these N-forms along successional gradients, affects tree distributions (Stewart et al 1988;Kronzucker et al 1997;Aidar et al 2003). In N-limited arctic and alpine tundra plant communities, species composition was found to correlate with the partitioning of differentially available forms of N, with dominance being linked to a species' ability to exploit the most abundant N-form (McKane et al 2002;Ashton et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that, in general, pioneer species, such as Cgl, have a preference for N-NO − 3 as their nitrogen source and have high levels of NRA. However, secondary species, such as Ima and Hco, have relatively low levels of this enzyme and a lower affinity for N-NO − 3 (Stewart et al, 1988(Stewart et al, , 1990Aidar et al, 2003;Pereira-Silva et al, 2011). Therefore, we highlight that variables such as NRA in plants and soil N-NO − 3 content can indicate the form of nitrogen nutrition appropriate for ecological restoration projects.…”
Section: Discussionmentioning
confidence: 99%
“…Trees differ in their ability to assimilate nitrate in their leaves (Smirnoff et al, 1984 (Stewart et al, 1988 (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%